HOW TO HANDLE THE PAPER LOAD (Authors: Gene Stanford (Chair) and the Committee on Classroom Practices) - Emery, Winston G. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1980)
Gene Stanford (Chair) and the Committee on Classroom Practices. HOW TO HANDLE THE PAPER LOAD. Urbana, Illinois: National Council of Teachers of English, 1979. 135 pp. $5.00.